Effectiveness of Police Response: Denver, 1982 - Bayley, David ([Verlag nicht ermittelbar], 1985)
This data collection investigates the nature of law enforcement by recording police behavior in problematic situations, primarily disturbances and traffic stops. The data collection contains two files. The first consists of information on disturbance encounters. Disturbance variables include type of disturbance, manner of investigation, designation of police response, several situational variables such as type of setting, number of victims, bystanders, suspects, and witnesses, demeanor of participants toward the police, type of police response, and demeanor of police toward participants. The second file contains data on traffic offenses. The variables include manner of investigation, incident code, officers' description of the incident, condition of the vehicle stopped, police contact with the passengers of the vehicle, demeanor of passengers toward the police, demeanor of police toward the passengers, and resolution of the situation. The data were collected based on field observation, using an instrument for recording observations.